Pointwise and uniform approximation by multivariate neural network operators of the max-product type. (September 2016) - Costarelli, Danilo; Vinti, Gianluca
Abstract: In this article, the theory of multivariate max-product neural network (NN) and quasi-interpolation operators has been introduced. Pointwise and uniform approximation results have been proved, together with estimates concerning the rate of convergence. At the end, several examples of sigmoidal activation functions have been provided.